An Analysis of the Preparatory School Questions for in the Biology Books on the Basis of the Brain-based Learning - Fadel Taleb Al-Masoudi, Abbas; Talib Al-Khuzai, Qasim; M. , Safaa Kamel Jaber (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to reveal the extent to which the book chapter questions consider the mental skills of the students according to the brain-based learning theory. The researchers used content analysis; they constructed a tool that was proved to be authentic and consistent in three fields, including twenty-three mental skills. The right and left lobes of the brain each include eight mental skills and seven skills in the lateral sides of the brain together. Then, the questions were analyzed. The results showed the skills in the left side of the brain were most frequent, while the mental ones were the least. It was noted that some abilities were outstanding, such as the critical and oral, while some others were neglected, such as the symbolic and metaphoric. The researchers provide some recommendations and suggestions for further studies.